The causal relationship between stock price and interest rate (evidence in Malaysia) / Muhammad Hafiz Rosli - Rosli, Muhammad Hafiz (2016)
This study examines the causal relationship between stock prices and interest rates. Interest rate is represented by the base lending rate of central bank of Malaysia, BNM and stock prices are collected from the Datastream BMSB 30. Secondary data, in the form of yearly observations for the period from year 2006 to 2015 had been utilized. Time series analysis and the Granger causality test is employed to examine the relationship. The results indicate that most of the companies are have no significant Causal Relationship between base lending rate and stock price. Only 8 companies that have a uni-directional Causal Relationship between base lending rate and stock price whether the base lending rate cause stock price or the stock price cause the base lending rate, such as company A3, B1 , K1, M2, P2, T1 , G2 and R1.